PENGEMBANGAN KAMPUNG COKLAT SEBAGAI AGROWISATA DI BLITAR JAWA TIMUR - Syaifulloh, Muhammad; Setiawan, Wahyu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2016)
Kampung Coklat is a tourist attraction of special interest in Blitar, East Java, an ecotourism. Tourist components that have been held, the product quality is maintained, Human Resources who has been there, security from both outside and within the company and also cooperation with local communities necessary for the development, enhancement, training, coaching and maintenance. It is intended to support the development which will be done so as not to compete with other competitors. People who play an active role and cooperation that has existed well into the main capital to undertake development . The role of the community has been proven to work and establish new jobs in Kampung Coklat . Besides the community to fully support the development of Kampung Coklat. Keywords: ecotourism , tourism , products